2016
DOI: 10.5114/aoms.2016.61916
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of cyclooxygenase-2 expression in patients with hepatocellular carcinoma: a meta-analysis

Abstract: IntroductionCyclooxygenase-2 (COX-2) is believed to be an important enzyme in the carcinogenesis of hepatocellular carcinoma (HCC). However, it is still controversial whether COX-2 expression can be regarded as a prognostic factor for HCC patients. We performed a systematic review and meta-analysis of studies assessing the clinical and prognostic significance of COX-2 expression in HCC.Material and methodsIdentification and review of publications assessing clinical or prognostic significance of COX-2 expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 27 publications
2
36
0
Order By: Relevance
“…The COX-2/PGE2 axis is a potential driver of HIF-2α expression and activity in HCC cells and HCC tissues under hypoxic conditions COX-2 is also upregulated in hypoxic HCC tissues and is associated with a poor prognosis in HCC patients; this relationship with HCC is similar to that of HIF-2α (10,11,16,18). COX-2 elicits its effects mainly through producing prostaglandins, especially PGE2 (20,21).…”
Section: Downregulation Of Hif-2α Inhibits the Tumour Development Andmentioning
confidence: 68%
See 1 more Smart Citation
“…The COX-2/PGE2 axis is a potential driver of HIF-2α expression and activity in HCC cells and HCC tissues under hypoxic conditions COX-2 is also upregulated in hypoxic HCC tissues and is associated with a poor prognosis in HCC patients; this relationship with HCC is similar to that of HIF-2α (10,11,16,18). COX-2 elicits its effects mainly through producing prostaglandins, especially PGE2 (20,21).…”
Section: Downregulation Of Hif-2α Inhibits the Tumour Development Andmentioning
confidence: 68%
“…Previous studies have also revealed that COX-2 can be induced by various stimuli, including hypoxia (15,16). In the context of HCC, COX-2 expression in tumour tissues is closely associated with the spontaneous initiation, development and treatment effects of HCC (17)(18)(19). As the predominant product of COX-2, prostaglandin E2 (PGE2) can achieve diverse biological effects primarily through its binding to a family of receptors to promote angiogenesis, cell survival and the metastasis of cancer cells (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, the increased expression of COX‐2 in HCC was associated with tumour differentiation, tumour growth and apoptosis . Chen et al reported that the expression of COX‐2 in patients with HCC is related to decreased overall survival and disease‐free survival in patients with HCC. A randomized controlled trial showed that use of meloxicam prevents the recurrence of HCC after curative therapy .…”
Section: Discussionmentioning
confidence: 99%
“…COX‐2‐selective inhibitors can inhibit the inflammatory response, cell proliferation, and angiogenesis and can induce cancer cell apoptosis. Previous studies have indicated that the overexpression of COX‐2 in glioma cells could affect the development of glioma, and an increase in COX‐2 expression is also associated with the histopathological grade and invasiveness of glioma, which ultimately lead to poor prognoses for patients . In general, reducing the expression of COX‐2 may be an effective alternative to inhibit glioma growth and promote apoptosis.…”
Section: Introductionmentioning
confidence: 99%